The Formation of Streptococcus mutans Persisters Induced by the Quorum-Sensing Peptide Pheromone Is Affected by the LexA Regulator - Leung, Vincent (J Bacteriol, 2015)
The presence of multidrug-tolerant persister cells within microbial populations has been implicated in the resiliency of bacterial survival against antibiotic treatments and is a major contributing factor in chronic infections. The mechanisms by which these phenotypic variants are formed have been linked to stress response pathways in various bacterial species, but many of these mechanisms remain unclear. We have previously shown that in the cariogenic organism Streptococcus mutans, the quorum-sensing peptide CSP (competence-stimulating peptide) pheromone was a stress-inducible alarmone that triggered an increased formation of multidrug-tolerant persisters. In this study, we characterized SMU.2027, a CSP-inducible gene encoding a LexA ortholog. We showed that in addition to exogenous CSP exposure, stressors, including heat shock, oxidative stress, and ofloxacin antibiotic, were capable of triggering expression of lexA in an autoregulatory manner akin to that of LexA-like transcriptional regulators. We demonstrated the role of LexA and its importance in regulating tolerance toward DNA damage in a noncanonical SOS mechanism. We showed its involvement and regulatory role in the formation of persisters induced by the CSP-ComDE quorum-sensing regulatory system. We further identified key genes involved in sugar and amino acid metabolism, the clustered regularly interspaced short palindromic repeat (CRISPR) system, and autolysin from transcriptomic analyses that contribute to the formation of quorum-sensing-induced persister cells.